Economic geology of sulphide nickel deposits - Harrison, P A (Rhodes University, Faculty of Science, Department of Geology, 1983)
From Chapter 1: It has been a long standing belief that many nickel sulphide ores are derivatives of magmatic processes in ultramafic and mafic rocks, and that they segregate from these magmas as immiscible sulphide droplets which are then concentrated into an orebody by gravitational settling either during intrusion or extrusion, or during the early stages of crystallization of the magma (Naldrett, 1981). Some geologists however, have suggested alternative mechanisms to explain the concentration of nickeliferous sulphides in the mafic and ultramafic hosts. These include hydrothermal replacement (Fleet, 1977), exhalative volcanic processes (Lusk, 1976), or major metamorphic upgrading of low grade, initially magmatic deposits (Barrett et al., 1977). It is not the purpose of this study to verify or disprove these hypotheses, but in so far as the initial concentration of sulphides in most deposits is concerned, these effects are relatively unimportant (Naldrett, 1981). The nickel sulphide ores associated with these mafic and ultramafic host rocks, invariably consist of nickeliferous pyrrhotite as the dominant phase, together with lesser, but variable, amounts of magnetite, pentlandite, chalcopyrite, cubanite, and platinum group elements (Reynolds, 1982).
Keywords: Nickel sulfide; Ore deposits; Geology, Economic; Silicate minerals; Geochemistry